2020
DOI: 10.1007/s00442-020-04806-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental heterogeneity on phenotypic variation of the endemic plant Lilium pomponium in the Maritime and Ligurian Alps

Abstract: Geographical limits of species’ distributions are assumed to be coincident with ecological margins, although this assumption might not always be true. Indeed, harsh environments such as Alpine and Mediterranean ecosystems may favour high phenotypic variability among populations, especially those in peripheral sites. Floral traits are often found to be less variable and less affected by environmental heterogeneity than vegetative traits because variation in the former may have negative effects on fitness. For t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 72 publications
(90 reference statements)
1
10
0
Order By: Relevance
“…These results provide a parallel with the previous studies of genetic variability in relation to distribution limits and potential ecologically marginality [ 27 , 28 ]. Casazza et al [ 28 ] insist on the probable effects of local topographic variation that blur any possible relation between genetic variation and distribution limits.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…These results provide a parallel with the previous studies of genetic variability in relation to distribution limits and potential ecologically marginality [ 27 , 28 ]. Casazza et al [ 28 ] insist on the probable effects of local topographic variation that blur any possible relation between genetic variation and distribution limits.…”
Section: Discussionsupporting
confidence: 86%
“…This may affect population dynamics and genetics irrespective of distance from the geographical centre of the range. Furthermore, Macrì et al [ 27 ] found no direct relationship between the presence near range limits and phenotypic performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may explain why some small-sized populations near the geographical center but far from environmental center (i.e., P04, P05 and P08 in Table 3) have high F ST and Jost'D values and low Rho values. In fact, the high number of flowers per inflorescence detected in these small populations may favor geitonogamous pollination among flowers on the same plant (Macrì et al, 2021). In small sized populations of facultative-autogamous species, like L. pomponium (Casazza et al, 2018), geitonogamy may assure the production of a small, but regular number of seeds (Roberts et al, 2014), but at the cost in terms of reduced outcrossing (Lloyd, 1992;Harder & Barrett, 1995).…”
Section: Genetic Structure and The Cphmentioning
confidence: 99%
“…Moreover, in L. pomponium population connectivity may be further reduced by a decrease in suitable habitat due to (i) shrubland or forest expansion in mid-elevation of high elevation sites (Carlson et al, 2014) and/or (ii) urbanization in peripheral coastal lowland areas (Noble & Diadema, 2011). Given that gene flow in perennial plants mainly occurs by pollen transfer (Levin & Kerster, 1974;Ennos, 1994;Tarayre et al, 1997), pollen limitation detected in the southernmost populations of L. pomponium may further drive the genetic differentiation among these populations (Macrì et al, 2021).…”
Section: Genetic Structure and The Cphmentioning
confidence: 99%